Isolation and Evaluation of Rhizopus arrhizus Strains from Traditional Rice Wine Starters (Jiuqu): Enzyme Activities, Antioxidant Capacity, and Flavour Compounds - Bo Wan; Tian Tian; Ying Xiong; Siqi Wang; Xinyu Luo; Weifang Liao; Pulin Liu; Lihong Miao; Ruijie Gao (Foods)
Seventy-eight autochthonous strains of Rhizopus arrhizus were isolated from rice wine starter samples across twenty-nine regions in China to evaluate their potential in traditional rice wine fermentation. Strains were assessed for enzyme activity, antioxidant properties, amino acid production, and volatile flavour compounds. Significant variation in enzyme activities was observed, with acidic protease activity ranging from 280 to 1023 U/g, amylase from 557 to 1681 U/g, and esterase from 370 to 2949 U/g. Strains W17 and W42 exhibited the highest enzyme activities and antioxidant capacities, with a total phenolic content of 828 mg/L, total flavonoids of 215 μg/L, and an ABTS scavenging rate of 96.3%. They also produced high levels of glutamic acid (up to 3083 mg/L), enhancing the flavour profile. Histamine levels were low, ranging from 8 to 205 μg/L, ensuring product safety. Analysis of volatile compounds identified 80 substances, including 16 key aroma-active compounds, contributing to a complex flavour profile. These results provide a basis for selecting R. arrhizus strains to optimise rice wine fermentation, addressing market demand for diverse and functional products.